The relationship between body mass index, body image, and sexual function: A survey on Iranian pregnant women - Mahtab Senobari; Elham Azmoude; Marziyeh Mousavi (Shahid Sadoughi University of Medical Sciences, 2019)
Background The prevalence of sexual problems is high during pregnancy. Despite this, there are limited data about the impact of physical and psychological factors such as body weight and body image on sexual function in pregnant women. Objective To investigate the relationship between body mass index, body image, and sexual function among pregnant women. Materials and Methods In this cross-sectional study, a total of 206 Iranian pregnant women (106 with normal weight and 100 overweight women) in their 2nd and 3rd trimesters of pregnancy were surveyed. Survey instruments included the Female Sexual Function Index and Multidimensional Body-Self Relations Questionnaire. Results The prevalence of female sexual disorder was 72.3% in this survey. Diminished sexual desire/appetite was the most common problem reported by the participants (37.9%). The mean score of sexual problem and body image were not significantly different among overweight and normal weight women in the 2nd (p = 0.945 and p = 0.800, respectively) and 3rd trimesters of pregnancy (p = 0.310 and p = 0.507, respectively). Further, there were no relationships between the body mass index plus body image and the total female sexual function score (p = 0.44 and p = 0.837, respectively). However, the relationship between the appearance evaluation with lubrication (p = 0.043) and subjective weight with two subscales of sexual satisfaction (p = 0.005) and orgasm (p = 0.019) were significant. Conclusion The findings from this study revealed that there were no relationships between body mass index plus body image score and the sexual function in pregnancy. Therefore, a further research is recommended to study other potential factors affecting sexual function during pregnancy.